A study on factors contributing job stress among nurses at Hospital Kuala Krai (HKK) / Rohaya Abdul Rahman - Abdul Rahman, Rohaya (2012)
Project paper titled “Factor contributing job stress among nurses at Hospital Kuala Krai, Kelantan” is conducted as partial requirement to fulfill the requirement as needed by the Faculty of Business Management, University Technology Mara (UiTM). The objectives of this study is to identify the factors that lead to job stress in Hospital Kuala Krai, Kelantan and to identify the significant relationship between Independent Variables (IV) and occupational stress in Hospital Kuala Krai, Kelantan. This research focuses on nurses at Hospital Kuala Krai, Kelantan which consist about 246 of the nurses according the different grade such as grade U42, U41, U36, U32, U29, U24 and U19. The total population is 246 of nurses at Hospital Kuala Krai, Kelantan. The researcher decides to distribute 150 questionnaires to the nurses at Hospital Kuala Krai,Kelantan. The sampling method that will be used is “simple random sampling”. The hypothesis testing shows that role conflict and unfavourable work environment are significance with job stress while work overload is not significance with job stress.